Chiral symmetry and pion-nucleon scattering - Pupin, J. C.; Robilotta, M. R. (World Scientific Publ Co Pte Ltd, 1997)
In this work, we study the influence of the way pious couple to nucleons in perturbative calculation of an observable in the pion-nucleon scattering.